ISLAMIC FINANCIAL LITERACY AMONG SHARIA BANKERS IN BANDAR LAMPUNG - Any Eliza; Vitria Susanti (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
This article reports the findings of Islamic Financial Literacy for Sharia bankers in Bandar Lampung specifically in terms of Islamic financial products and what factors influencing it. The skill is needed to assist transactions, with a clear understanding and appreciation of the unique characteristics and features of Islamic Finance and its real economic value. As mentioned by the Financial Authority Service, one of the challenges that Sharia banking encounters are the inadequacy of capable and highly qualified human resources to support the development of sharia financial products and services. However, up to now there is a lack of studies about Islamic financial literacy in Indonesia, particularly for people who works on Islamic financial sectors. The objectives of this study are (i) to indicate the level of Islamic financial literacy among human resources of Sharia banks in Bandar Lampung, and (ii) to identify significant factors that influence Islamic financial literacy among the bankers. In terms of Islamic Financial Literacy rate, the result of the study is quite distinct from the existing research finding in that it shows that female bankers have higher Islamic Financial Literacy rate than their male counterpart. In addition, based on length of work and age cohort, the median groups also have higher Islamic financial literacy rate. While in terms of type of institution, bankers of Sharia banks exhibit advanced Islamic financial knowledge than Rural sharia banks’ staffs.  Using Factor Analysis, the study finding revealed the five factors determining Sharia banker’s Islamic financial literacy.========================================================================================================Literasi Keuangan Islam para Bankir Syariah di Bandar Lampung. Artikel ini menyajikan temuan pada studi yang mengidentifikasi faktor-faktor yang mempengaruhi Literasi Keuangan Islam untuk bankir Syariah di Bandar Lampung, khususnya dalam hal produk dan jasa keuangan Islam. Keahlian ini diperlukan untuk membantu transaksi, dengan pemahaman dan apresiasi yang jelas terhadap karakteristik dan fitur unik serta nilai ekonomi riil keuangan Islam. Sebagaimana disebutkan oleh Otoritas Jasa Keuangan bahwa salah satu tantangan yang dihadapi perbankan Syariah adalah tidak memadainya sumber daya manusia yang berkemampuan dan berkualifikasi tinggi untuk mendukung pengembangan produk dan layanan keuangan syariah. Namun, hingga saat ini hanya sedikit studi tentang literasi keuangan Islam di Indonesia, terutama bagi orang-orang yang bekerja di sektor keuangan Islam. Tujuan dari penelitian ini adalah (i) untuk menunjukkan tingkat literasi keuangan syariah sumberdaya manusia bank syariah di Bandar Lampung, dan (ii) untuk mengidentifikasi faktor-faktor signifikan yang mempengaruhi literasi keuangan syariah para banker tersebut. Dalam hal tingkat Literasi Keuangan Islam, hasil penelitian ini cukup berbeda dari temuan penelitian yang ada karena menunjukkan bahwa banker perempuan memiliki tingkat Literasi Keuangan Islam yang lebih tinggi daripada rekan pria mereka. Selain itu, berdasarkan lama bekerja dan kelompok usia, kelompok median juga memiliki tingkat melek finansial Islam yang lebih tinggi. Berdasarkan jenis institusi, bankir bank Syariah menunjukkan pengetahuan keuangan Islam yang lebih baik daripada staf BPRS. Dengan menggunakan Analisis Faktor, temuan penelitian ini mengungkapkan lima faktor yang menentukan literasi keuangan Islam bankir.